2018
DOI: 10.1016/j.jbusres.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Managing patterns of internationalization, integration, and identity transformation: The post-acquisition metamorphosis of an Arabian Gulf EMNC

Abstract: In this paper, we study the multifaceted transformation of an emerging market firm making multiple acquisitions. Drawing on a process study of an acquisitions program spanning two decades, we examine the post-acquisition internationalization, integration and organizational identity dynamics of an Arabian Gulf EMNC serial acquirer. We find that the serial acquisitions and post-acquisition integration were sufficiently profound and changing over time to create an organizational identity transformation in four ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 124 publications
0
15
0
Order By: Relevance
“…However, in the presence of too much resource similarity between acquirer and target, especially in relation to market and product resources, granting too much target brand management autonomy will inevitably lead to the brands from the acquirer and target firm to compete for core resource, causing brand perception confusion in the original customers (Vũ et al, 2009). In this case, emerging market firms conducting international M&As should adopt unified global brand management strategies aimed at constructing coherent organizational identities (Park et al, 2018). In the presence of high levels of target brand autonomy and strong resource similarity, the target TMT tends to resist the changes brought about by restructuring (Zollo and Singh, 2004), to hinder effective control of the target resources by the acquirer firm, and to impede the acquirer from directly accessing heterogeneous network resources and improving its network position.…”
Section: Integration Mode and Network Position When The Resources Of mentioning
confidence: 99%
“…However, in the presence of too much resource similarity between acquirer and target, especially in relation to market and product resources, granting too much target brand management autonomy will inevitably lead to the brands from the acquirer and target firm to compete for core resource, causing brand perception confusion in the original customers (Vũ et al, 2009). In this case, emerging market firms conducting international M&As should adopt unified global brand management strategies aimed at constructing coherent organizational identities (Park et al, 2018). In the presence of high levels of target brand autonomy and strong resource similarity, the target TMT tends to resist the changes brought about by restructuring (Zollo and Singh, 2004), to hinder effective control of the target resources by the acquirer firm, and to impede the acquirer from directly accessing heterogeneous network resources and improving its network position.…”
Section: Integration Mode and Network Position When The Resources Of mentioning
confidence: 99%
“…Concomitant with the scope of the phenomenon, scholars of acquisition programs have changed the unit of analysis from single deals to acquisition programs (Chatterjee, ). While the learning and performance effects of acquisition programs have been studied (e.g., Barkema et al, ; Zollo and Singh, ), only more recently has attention been directed to the evolution of innovation in acquisition programs, for instance, through identifying and growing knowledge resources cumulatively (Capron and Mitchell, ) or through internationalization and identity transformation based in part on innovation capabilities enhanced in iterative acquisitions (Park et al, ). These findings signal the potential for innovation development in acquisition programs and call for delving further into the dynamics of acquisition program processes and outcomes.…”
Section: Innovation Acquisition Programs and Ambidexteritymentioning
confidence: 99%
“…Over time it has become apparent that any single acquisition cannot provide an ongoing innovation momentum. Scholars have consequently dedicated increasing attention to acquisition programs (Smit and Moraitis, 2010;Park et al, 2018;Weber et al, 2018). Beyond the impact of single deals, acquisition programs can further leverage innovation capabilities obtained from targets, from different countries, acquired at different times (Laamanen and Keil, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have explored the EMNC's engagement with the institutional complexity faced in the foreign markets (Agnihotri & Bhattacharya, 2018;Liu, Öberg, Tarba, & Xing, 2018;Muralidharan et al, 2017;Park, Meglio, Bauer, & Tarba, 2018). Research has shown postacquisition integration change over time and can lead to changes in the organizational identity.…”
Section: Corporate Name Change and Postacquisition Performancementioning
confidence: 99%